Pharmacokinetics/Pharmacodynamic (PK/PD) relationship of therapeutic monoclonal antibodies used in oncology: what's new?. (March 2020) - Mir, Olivier; Broutin, Sophie; Desnoyer, Aude; Delahousse, Julia; Chaput, Nathalie; Paci, Angelo
Abstract: Monoclonal antibodies in oncology, used as targeted molecular therapy, linked to cytotoxic compound or directed against immune checkpoints, feature complex PKs essentially determined by their physicochemical characteristics. The increasing number of studies shows the existence of Pharmacokinetics/Pharmacodynamic (PK/PD) relationships for many of them. Although more studies, especially conducted in early clinical phases, are needed, existing studies highlight the need to integrate PK data for monoclonal antibodies in all phases of their development and the therapeutic management of patients with cancer. The current challenge is to identify non-responders as soon as possible. The use of monoclonal antibody dosage to determine the patient's PK profile and, as a result, the disease activity profile could therefore be an early predictive marker to help physicians optimise the strategy to be pursued, including dose adjustment, prolongation of the dose interval or even discontinuation of treatment. Highlights: PKs of monoclonal antibodies (mAbs) differ significantly from small molecules. Distribution is limited to the blood and lymph. Elimination is mainly due to cellular uptake depending on binding and targets. Target-mediated drug disposition gives an inherent relationship between PK and PD. Patient's PK profiles and parameters could be efficient predictive marker of efficacy.